Una nueva especie gipsófila de Sisyrinchium (Iridaceae: Sisyrinchieae) de México - Espejo Serna, Adolfo; Lopez-Ferrari, Ana Rosa; Ceja Romero, Jacqueline (Instituto de Ecología, A.C., 1998)
A new gypsophilous species of Sisyrinchium from the municipio of Villa Juárez in the state of San Luis Potosí, México is described and illustrated. S. zamudioi Espejo, López Ferrari & Ceja is recognized by its glaucous, slender, wiry stems ash-grey when dried and by its relatively small and ovate spathes.